Diabetic macular edema treated with ranibizumab following bevacizumab failure in Israel (DERBI study). Issue 2 (March 2019) - Ehrlich, Rita; Pokroy, Russell; Segal, Ori; Goldstein, Michaella; Pollack, Ayala; Hanhart, Joel; Barak, Yoreh; Kehat, Rinat; Shulman, Shiri; Vidne, Orit; Abu Ahmad, Wiessam; Chowers, Itay
Purpose: To evaluate the outcome of second-line intravitreal ranibizumab treatment in eyes with diabetic macular edema having persistent edema following initial therapy with intravitreal bevacizumab. Methods: Diabetic macular edema treated with ranibizumab following bevacizumab failure in Israel was a retrospective, multi-center study. Consecutive eyes with persistent diabetic macular edema following at least three previous intravitreal bevacizumab injections prior to intravitreal ranibizumab, at least three-monthly intravitreal ranibizumab injections and at least 12 months of follow-up were included. Data collected included demographics, ocular findings, diabetes control, details of intravitreal bevacizumab and ranibizumab injections, and visual and anatomical measurements before and after intravitreal ranibizumab treatment. Results: In total, 202 eyes of 162 patients treated at 11 medical centers across Israel were included. Patients received a mean (±standard deviation) of 8.8 ± 4.9 intravitreal bevacizumab injections prior to the switch to intravitreal ranibizumab. A mean of 7.0 ± 2.7 intravitreal ranibizumab injections were given during the 12 months following the switch to intravitreal ranibizumab. The median central subfield retinal thickness (±interquartile range) by spectral-domain optical coherence tomography decreased from 436 ± 162 µm at baseline to 319 ± 113 µm at month 12 (p < 0.001). Median logMAR visual acuity (±interquartile range) improved from 0.40 ± 0.48 at baseline to 0.38 ± 0.40 at month 12 (p = 0.001). Linear regression suggested that higher number of intravitreal ranibizumab injections and higher pre-switch central subfield retinal thickness were associated with favorable visual outcome. Higher number of intravitreal bevacizumab injections and the presence of intraretinal fluid before the switch lessened the odds of favorable outcome. Conclusion: Switching from bevacizumab to ranibizumab in persistent diabetic macular edema was associated with anatomical improvement in the majority of eyes and ⩾2 lines of vision improvement in 22% of eyes.